2020
DOI: 10.1097/md.0000000000018536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of therapeutic ERCP in patients with ectopic papilla of Vater

Abstract: It remains challenging for endoscopists to manage pancreaticobiliary diseases in patients with ectopic papilla of Vater by endoscopic retrograde cholangiopancreatography (ERCP). The present study sought to evaluate the efficacy and safety of ERCP for this issue. Consecutive patients with ectopic papilla of Vater who underwent initial ERCP due to pancreaticobiliary diseases were retrospectively analyzed. One hundred seven patients with ectopic papilla of Vater were included. The success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Hong et al. 12 recently reported that the success rate of cannulation for 107 patients with an ectopic papilla of Vater was 83.2%. They reported that the ectopic opening was so obscure that it may have increased the difficulty of cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hong et al. 12 recently reported that the success rate of cannulation for 107 patients with an ectopic papilla of Vater was 83.2%. They reported that the ectopic opening was so obscure that it may have increased the difficulty of cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the ectopic opening was so obscure that it may have increased the difficulty of cannulation. 12 Sfarti et al. 13 reported that a periampullary diverticulum can increase the rate of difficult or failed cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonography (US) is the most commonly used non-invasive imaging modality in the evaluation of the hepatobiliary system and the exocrine pancreas in dogs, offering high sensitivity but often lacking speci city, especially in patients with biliary and pancreatic ductal problems [4]. Endoscopic retrograde cholangiopancreatography (ERCP) has been proven to be an applicable, direct technique for evaluating hepatobiliary and pancreatic disorders both in human and veterinary medicine [5,6,7,8,9,10]. It is a minimally invasive technique, which combines endoscopy and uoroscopy to image the biliary system (endoscopic retrograde cholangiography, ERC) and pancreatic duct (endoscopic retrograde pancreatography, ERP).…”
Section: Introductionmentioning
confidence: 99%